PENGAPLIKASIAN EKSTRAK PEKTIN KULIT PISANG RAJA (Musa sapientum L) DAN KULIT PISANG KEPOK (Musaparadisiaca L) PADA SELAI TOMAT (Solanum lycopersicum) - Sucitra Sucitra; Andi Sukainah; Amirah Mustarin (Jurnal Pendidikan Teknologi Pertanian, 2018)
This study aims to determine the effect of addition of banana king skin pectin extract and extract pectin banana kepok skin to physical and chemical characteristics of tomato jam. This research was an experimental research with a complete factorial randomized design consisting of two factors with variation of banana peel extract (banana peel king and banana peel kepok) with pectin concentration (0.5% and 0.6%) was done with 4 treatments and 3 times repetition. The variables observed were methoxyl pectin test, hedonic test, water content test, pH value test, sucrose and pectin test. The analytical technique used in this study is the analysis of variance analyzed using SPSS version 20. The results showed that banana peel pectin extract did not affect the color, taste, and aroma of tomato jam but only affect the texture of tomato jam produced. The best tomato jam was obtained from the addition of extract pectin banana husk 0.6% with 2.78% methoxyl content, 33.58% moisture content, 2.73% pH, 65.28% sucrose content, and 0.81% pectin content.